EVALUASI CONTROL ACTIVITIES ATAS INVENTORY BERDASARKAN COSO INTERNAL CONTROL FRAMEWORK PADA UD BALI RAYA DI TABANAN - Irma Cahyani Kawi (Perpustakaan Universitas Surabaya, 2019)
Abstract - The results of the analysis and discussion show that the COSO Framework can be implemented in medium-sized enterprises, but not all points in the COSO Framework can be applied well, because in the small and medium enterprises the main emphasis is on the control environment and monitoring, but not the three points others are risk assessments, control activities, and information and communication which also play an important role in internal control. UD Bali Raya is a business entity engaged in the field of trade goods and services. Can be seen if the control activities UD Bali Raya still weak because of the job description is less clear and inadequate documents, so there is still a sequence of functions that occur that can lead to abuse of authority. Recording and documentation is still inadequate. The lack of knowledge of internal controls also makes the owners of UD Bali Raya does not know the controls that should be done on the business. Keywords: Internal Control, COSO, Inventory, Effective, and Automotive.